2019
DOI: 10.1159/000504303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NLRP3 Protects Human Lens Epithelial Cells against Oxidative Stress-Induced Apoptosis by NF-κB Signaling

Abstract: <b><i>Backgrounds/Aims:</i></b> To explore whether NLRP3 is involved in the development of cataract and to study the effect of NLRP3 on hydrogen peroxide (H<sub>2</sub>O<sub>2</sub>)-induced injury in human lens epithelial cells. <b><i>Methods:</i></b> Oxidative stress-induced apoptosis model was constructed by treating HLEB3 cells with 50 µM H<sub>2</sub>O<sub>2</sub> at different times (6 h, 12 h) and was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Yan et al found that the increased expression of laminin α4 in the anterior lens capsule is the main mechanism leading to the occurrence of ARC [16], which is consistent with our transcriptome sequencing results. Moreover, the inhibition of NLRP3 was shown to reduce oxidative stress-induced damage to human lens epithelial cells, while NLRP3 protein expression was significantly increased in lens epithelial cells under oxidative stress [17], which was also consistent with our verification results. However, more than 80% of the genes identified by transcriptome sequencing in this study have not previously been associated with ARC, so should be explored in future in-depth studies.…”
Section: Discussionsupporting
confidence: 91%
“…Yan et al found that the increased expression of laminin α4 in the anterior lens capsule is the main mechanism leading to the occurrence of ARC [16], which is consistent with our transcriptome sequencing results. Moreover, the inhibition of NLRP3 was shown to reduce oxidative stress-induced damage to human lens epithelial cells, while NLRP3 protein expression was significantly increased in lens epithelial cells under oxidative stress [17], which was also consistent with our verification results. However, more than 80% of the genes identified by transcriptome sequencing in this study have not previously been associated with ARC, so should be explored in future in-depth studies.…”
Section: Discussionsupporting
confidence: 91%
“…[3][4][5] Studies have confirmed that cataracts are directly related to the apoptosis of LECs caused by oxygen free radicals. 6,7 Thus, it is important to explore antioxidant drugs that can prevent the formation and development of cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…AS‐IV possesses many pharmacological activities, such as antioxidative stress, anti‐inflammation via regulating various signaling pathways (L. Li et al, 2017). For instance, AS‐IV inhibited inflammatory response and oxidative stress via inhibition of MAPK signaling pathway (Hsieh et al, 2020), and AS‐IV also exhibited inhibitory effect on NLRP3 inflammasome (Leng et al, 2019; Xie et al, 2020), which protected HLECs from H 2 O 2 ‐induced apoptosis and inflammatory response via inhibition of NF‐κB signaling pathway (Zou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…AS‐IV protected against retinal iron overload toxicity through regulation of iron activity and inhibition of NF‐κB and MAPKs signaling activation (Song et al, 2021). Various studies have shown that AS‐IV exhibited suppressive effect on NLRP3 inflammasome (Leng et al, 2019; Xie et al, 2020), and inhibition of NLRP3 was able to protect HLECs from H 2 O 2 ‐induced apoptosis and inflammatory response by inhibiting the NF‐κB signaling pathway (Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%